A COMPARATIVE STUDY OF THE INTELLECTUAL AND POLITICAL VISSION OF SYED JAMAL-U-DIN AFGHANI AND SIR SYED AHMAD KHAN - Sajid Hussain, Sohail Akhtar, Sajeela Parveen, Romeesa Najeeb (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Ideological tendencies are of special importance in the rise and fall of nations. The rise of every nation begins with the views expressed by thinkers. When in the opinion of thinkers, most of the people of the nation or a few people of leadership ability are included; they lead the nation to the heights and heights. Similarly, when the nation rises, political stability as well as internal stability, peace and in the promotion of peace, economic and social security, the practice of high moral values ??and the spread of knowledge and wisdom, that nation is far ahead of other nations.On the other hand, it is a fact that the beginning of the fall is associated with the fall of thought. Whenever there is an intellectual decline, the tendency of imitation increases in the nations and the development of knowledge and wisdom stops, the morals of the nations become scattered, the war of interests begins and it has a bad effect on peace and order. As a result, internal stability weakens and the nation gradually loses political dominance.Another fact is that when a nation is on the verge of ascension, at some point its intellectual decline begins which is now hidden behind the veil of ascension but its effects gradually appear later. Thus, when a nation declines, its intellectual rise begins to reach its destination. If this intellectual rise is supported by the people and the leaders, then the political rise begins.The period of Afghani and Sir Syed was period of political decline of the Muslims, so both the personalities felt the need for intellectual development but there are fewer similarities and more differences in the ideological views of Afghani and Sir Syed because both were looking the political down-fall of Muslim Ummah in different perspective. Sir Syed Ahmad Khan and Jamal-u-Din Afghani guided the Muslims through modern education and unity. This Paper highlights the intellectual and political thinking of Syed Jamal-uu-Din Afghani and Sir Syed Ahmad Khan.